MRI of intestinal endometriosis. (March 2021) - Bazot, Marc; Kermarrec, Edith; Bendifallah, Sofiane; Daraï, Emile
Abstract: Endometriosis is a common gynecological condition of unknown etiology, which mainly affects women of reproductive age. The commonest site of gastrointestinal endometriosis is the rectosigmoid colon. Involvement of the sigmoid, cecum, appendix, and small bowel are less common, but one third of rectosigmoid endometriosis is associated with right-sided extra-pelvic bowel endometriosis. Intestinal endometriosis represents one of the most severe forms of deep endometriosis (DE). Magnetic resonance imaging (MRI) is recommended as a second-line technique in the preoperative workup of DE, especially for gastrointestinal endometriosis. An optimal MRI protocol is required for a complete mapping of endometriotic lesions. MRI could be used as a triage test in the diagnosis of rectosigmoid colon endometriosis. Magnetic resonance enterography should be additionally performed requiring a specific additional MRI protocol for the evaluation of multicentric intestinal endometriotic lesions. Except other imaging techniques, the aim of this chapter is to expose indications for MRI, technical requirements, patient preparation, MRI protocols, and criteria for the diagnosis of intestinal endometriosis. Highlights: Bowel preparation is highly recommended before magnetic resonance imaging (MRI) to diagnose rectosigmoid endometriosis. T2-weighted MRI sequences are the reference standard to diagnose intestinal endometriosis. Intestinal wall thickening with low signal on T2-weighted image is robust to diagnose deep endometriosis.